Determinan Keberhasilan Penerapan Sistem Akuntansi Instansi Berbasis Akrual Dalam Penyusunan Laporan Keuangan Pemerintah - Irfani, Muhajir; Pituringsih, Endar; Hamdani Husnan, Lalu (E-Jurnal Akuntansi; Vol 30 No 6 (2020), 2020)
The manifestation of the application of government accounting standards is the WTP opinion from BPK. This study aims to examine the effect of financial staff education, accounting training, the use of the SAIBA application, and organizational commitment to the successful application of an accrual-based accounting system. This research was conducted at the Land Office work unit within the scope of the NTB Province BPN Regional Office. Respondents numbered 63 people. Data analysis techniques used multiple linear regression analysis. The results showed that organizational commitment had a positive effect, the use of the SAIBA application had a negative effect, but financial staff education and accounting training had no effect on the successful application of the accrual-based agency accounting system. Keywords: Financial Staff Education; Accounting Training; SAIBA; Organizational Commitment; Accrual Based Institution Accounting System.